Effectiveness of a career intervention for empowerment of institutionalized youth - Ana Daniela Silva, A.D. (2017)
This study evaluated the effectiveness of a brief and structured career adaptability intervention for institutionalized youth. The intervention included six weekly 90-min sessions. Participants were 22 youths aged 14-18 years (M-age = 15.09; SD = 1.269, 81.8% boys). Participants were divided in two groups: an experimental group (n = 16) and a control group (n = 6). Both groups completed the Career Adapt-Abilities Scale, the Positive Affect Scale and the Satisfaction with Life Scale in two occurrences of measurement (pre- and posttest). The experimental group completed the Session's Self-Evaluation Questionnaire to evaluate the intervention process. Results indicated statistically significant differences between the groups. The experimental group improved in the majority of the career adaptability and affective dimensions. This group also presented a high effect size in most career adaptability dimensions (>.70) but a lower one in the affective dimensions (<.20). The process evaluation indicated few negative session comments. These results sustain the promising role of this intervention, which should continue to be further investigated. This study highlights the need to advance career research and practice with institutionalized youths.